Hydromechanical behavior of a natural swelling soil of Boumagueur region (east of Algeria) - Mebarki, Mehdi; Kareche, Toufik; Derfouf, Feth-Ellah Mounir; Taibi, Said; Abou-Bekr, Nabil (Geomechanics and Engineering, 2019)
This work presents an experimental study of the hydromechanical behavior of a natural swelling soil taken from Boumagueur region east of Algeria. Several pathological cases due to the soil shrinkage / swelling phenomenon were detected in this area. In a first part, the hydric behavior on drying-wetting paths was made, using the osmotic technics and saturated salts solutions to control suction. In The second part, using a new osmotic oedometer, the coupled behavior as a function of applied stresses and suction was investigated. It was shown that soil compressibility parameters was influenced by suction variations that an increase in suction is followed by a decrease in the virgin compression slope. On the other hand, the unloading slope of the oedometric curves was not obviously affected by the imposed suction. The decrease in suction strongly influences the apparent preconsolidation pressure, ie during swelling of the samples after wetting.